The Mathematical Thinking Among Muslims and Its Impact on the Science of Inheritance - Klaina, Mekki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The challenge I faced while teaching the inheritance course to students unfamiliar with this field and its terminology was evident in their difficulty in easily understanding the scientific material, requiring considerable time for explanation. This situation prompted me to seek a way to simplify their understanding of inheritance. Given the mathematical nature of the course and the students' familiarity with this area, so I decided to utilize this aspect to achieve my teaching objectives, eventually developing mathematical rules that clarify the distribution of inheritance among heirs. This approach not only helped me achieve my goals but also led me to connect the efforts of Muslims with mathematics, highlighting their creativity in this domain, which continues to this day. Therefore, in my teaching methodology, I relied on both library research and mathematical approaches. The research highlighted the contributions of Muslims to mathematics and I introduced some of my own rules, applying them specifically to the topic of intersex cases.